O05 Barriers and facilitators to accessing and using online sexual healthcare services among populations who have never used or struggled to use online sexual healthcare services, within the SEQUENCE digital research programme. (16th June 2022) - McLeod, Julie; MaDonald, Jennifer; Estcourt, Claudia; Owusu, Melvina Woode; Lloyd, Karen; Greevenbroek, Roos van; Gibbs, Jo; Mapp, Fiona; Bloch, Sonja; Blandford, Ann; Saunders, John; Flowers, Paul
Abstract : Introduction: Online sexual health services could widen access to sexual healthcare. However, some may struggle to use online services for various reasons, such as low socio-economic status and learning difficulties 1 . To inform development of an inclusive and accessible eSexual Health Clinic (eSHC 2 ), this study aims to detail barriers and facilitators (B&Fs) to using online sexual health services among populations who may struggle. Methods: Using the PROGRESS+ framework 3 to inform purposive sampling, we recruited diverse participants (N=35) who had struggled to/never used online sexual health services, across NHS Trusts/Health boards and UK community-based organisations. Interviews investigated B&Fs to accessing sexual health information and advice online, ordering and returning STI self-sampling kits, getting STI results online, completing an online treatment consultation and accessing treatment. We extracted and tabularised B&Fs to each element of the care pathway. Results: Barriers included lack of familiarity with online services; perceived impersonal nature of online sexual healthcare; concerns about ability to self-sample correctly and about misunderstanding questions/information leading to incorrect treatment. Facilitators included perceived anonymity and protection from judgement; convenience; many sexual healthcare needs being met discretely in one place; and perception that online NHS services could be trusted. Discussion: Among disadvantaged populations, the eSHC could overcome some barriers to using sexual healthcare, such as embarrassment. However, it introduces novel barriers, including important concerns about misunderstanding information or questions leading to incorrect care and online services feeling too impersonal. Further analysis will develop theory-and-evidence-based recommendations to overcome modifiable barriers and optimise online sexual healthcare for inclusivity. References: Robinson L, Schulz J, Blank G, Ragnedda M, Ono H, Hogan B, Mesch G, Cotten SR, Kretchmer SB, Hale TM, Yan P. Digital inequalities 2.0: Legacy inequalities in the information age. First Monday, University of Illinois at Chicago Library, 2020; 25(7): 10.5210/fm.v25i7.10842. halshs-02889893 Estcourt CS, Gibbs J, Sutcliffe LJ, Gkatzidou V, Tickle L, Hone K, Aicken C, Harding-Esch EM, Eaton S, Oakeshott P, Szczepura A. The eSexual Health clinic system for sexually transmitted infection management, prevention and control: exploratory studies demonstrating safety, feasibility and public health utility. The Lancet Public Health. 2017 Mar 18; 2(4): e182-e190. https://doi.org/10.1016/S2468-2667(17)30034-8 O'Neill J, Tabish H, Welch V, Petticrew M, Pottie K, Clarke M, Evans T, Pardo Pardo J, Waters E, White H, Tugwell P. Applying an equity lens to interventions: using PROGRESS ensures consideration of socially stratifying factors to illuminate inequities in health. Journal of Clinical Epidemiology. 2014; 67(1): 56-64. http://doi.org/10.1016/j.jclinepi.2013.08.005